Improving the Production Process of Line Gen for Furniture Production - Sriyanalugsana, Suphattra; Punsri , Kitikul (Thai Industrial Engineering Network Journal, 2024)
Furniture is an important part of home and condo decoration. The case study factory is a furniture factory where the Line Gen production process is responsible for producing sample furniture as well as managing various repairs and work that is returned for repairs. The production process focuses on the speed of production. Currently, there are problems with returns and rejected work in the production process of Line Gen. There were errors in determining delivery dates and preparing raw materials for production, including the lack of clear coordination among each relevant department, resulting in production work exceeding the delivery deadline. There were thus delays in the production of furniture. Therefore, in order to solve these problems, this research has prepared a standard work manual (Work Instructions: WI) and a production sequence plan checklist, including capacity analysis. The results show that before the improvement, 80 returned jobs were generated, of which 38 exceeded the transfer date of 47.5%, and the number of days beyond the average transfer period was 2.42 days. After the improvement, 68 jobs were returned, 17 of which exceeded the transfer deadline (25%), and the days beyond the transfer deadline decreased on average to 1.47 days. In the case of rejecting jobs before improvement, there was a total of 96 jobs, 77 of which were beyond the transfer date of 80.2%, and the number of days beyond the average transfer period was 4.56 days. After improvements, there were 98 rejected jobs, with 49 jobs exceeding 50% of the transfer date, and we were able to reduce the average transfer overdue days to 2.24 days.